2003
DOI: 10.1002/cbic.200300700
|View full text |Cite
|
Sign up to set email alerts
|

NMR Spectroscopy of RNA

Abstract: NMR spectroscopy is a powerful tool for studying proteins and nucleic acids in solution. This is illustrated by the fact that nearly half of all current RNA structures were determined by using NMR techniques. Information about the structure, dynamics, and interactions with other RNA molecules, proteins, ions, and small ligands can be obtained for RNA molecules up to 100 nucleotides. This review provides insight into the resonance assignment methods that are the first and crucial step of all NMR studies, into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
398
1
11

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 462 publications
(445 citation statements)
references
References 148 publications
20
398
1
11
Order By: Relevance
“…By one-dimensional NMR spectroscopy, we found that Lin28-binding RNAs contain imino resonances from 10 to 12.2 ppm, indicative of non-canonical hydrogen bonds (48,51,60). The imino resonance pattern is characteristic of the G:G:G:G hydrogen-bonding networks found in G4s (48,51,61).…”
Section: Discussionmentioning
confidence: 88%
“…By one-dimensional NMR spectroscopy, we found that Lin28-binding RNAs contain imino resonances from 10 to 12.2 ppm, indicative of non-canonical hydrogen bonds (48,51,60). The imino resonance pattern is characteristic of the G:G:G:G hydrogen-bonding networks found in G4s (48,51,61).…”
Section: Discussionmentioning
confidence: 88%
“…Nonexchangeable and exchangeable resonance assignments (BMRB deposition 6509) were obtained by using standard methodologies (see Supporting Methods, which is published as supporting information on the PNAS web site) (30) at 25°C and 10°C, respectively. NMR experiments were acquired on Varian Inova 500 MHz (Texas A&M University), Varian Inova 600 MHz (Texas A&M University͞Scripps Research Institute), or Bruker 900 MHz (Scripps Research Institute) spectrometers.…”
Section: Methodsmentioning
confidence: 99%
“…The GSR apt -RNA comprises 73 nucleotides and is at the upper size limit for NMR analysis (32). To obtain site-resolved information by one-dimensional real-time NMR methods, selective isotope labeling of the RNA in combination with NMR filter experiments (33) was used.…”
Section: Two-mentioning
confidence: 99%